TIGIT acts as an immune checkpoint upon inhibition of PD1 signaling in autoimmune diabetes - Trivedi, Prerak; Jhala, Gaurang; De George, David J.; Chiu, Chris; Selck, Claudia; Ge, Tingting; Catterall, Tara; Elkerbout, Lorraine; Boon, Louis; Joller, Nicole; Kay, Thomas W.; Thomas, Helen E.; et al. (Frontiers in Immunology, 2024)
Chronic activation of self-reactive T cells with beta cell antigens results in the upregulation of immune checkpoint molecules on these self-reactive T cells. These immune checkpoint pathways keep selfreactive T cells under control and delay beta cell destruction in autoimmune diabetes. Inhibiting PD1/PD-L1 immune checkpoint signaling results in autoimmune diabetes in mice and humans with pre-existing autoimmunity against beta cells. However, it is not known if other immune checkpoint molecules, such as TIGIT, can also negatively regulate self-reactive T cells. TIGIT negatively regulates the CD226 costimulatory pathway, T cell receptor (TCR) signaling and hence T cell function. Here, we show that TIGIT is highly expressed on activated islet infiltrating T cells in non-obese diabetic (NOD) mice. Single cell RNA sequencing analysis of islet infiltrating T cells identified a subset of stem-like memory CD8+ T cells expressing multiple immune checkpoints including TIGIT, PD1 and the transcription factor EOMES, which is linked to dysfunctional CD8+ T cells. A known ligand for TIGIT, CD155 was expressed on beta cells and islet infiltrating dendritic cells. However, despite TIGIT and its ligand being expressed on CD8+ T cells and beta cells respectively, islet infiltrating PD1+ TIGIT+ CD8+ T cells were functional. Inhibiting TIGIT alone in prediabetic NOD mice did not result in exacerbated autoimmune diabetes while inhibiting PD1-PDL1 signaling resulted in rapid autoimmune diabetes, indicating that TIGIT does not restrain islet infiltrating T cells in autoimmune diabetes to the same degree as PD1. Interestingly, partial inhibition of PD1-PDL1 in combination with TIGIT inhibition resulted in rapid diabetes in NOD mice. These results suggest that TIGIT and PD1 act in synergy as immune checkpoints when PD1 signaling is partially impaired. In summary, beta cell specific stem-like memory T cells retain their functionality despite expressing multiple immune checkpoints and TIGIT is below PD1 in the hierarchy of immune checkpoints in autoimmune diabetes.